Religious Understanding Strategy with Kitab Kuning Media in Students’ Dormitories - Annurani, Achmad Husein; Shofiyullah, Muhammad; Dhiyaul Haq, Muhammad Naufal; Prabowo, Sugeng Listyo (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This article explores how the Kitab Kuning media in student dormitories can influence and deepen their religious understanding. This study aims to analyze the role of the Kitab Kuning in increasing religious insight and its impact on the spiritual life of students in the dormitory environment. The research method involves a qualitative approach through in-depth interviews and participatory observation. The results of the study confirm that the Kitab Kuning makes a positive contribution to understanding complex religious concepts, provides tools for students to overcome religious dilemmas, and strengthens their recognition of religious identity